(3eONd cej dEOGQI GdCNWGQ hQjGVjGJ GdeGd hGdGSJKeGQs - (3CMeO YHO Gddg beMGhj(B, (3CHGXeIs ((3GdQjGV(B:s (3eWHYI GdGTYGY GdafjI(B,s, 2002)
(3EOGQI GdCNWGQ(B- (3QjGVjGJ GdeGd hGdGSJKeGQs
(3LOGhd eGdjI U(B.263s
Keywords: (3GdEOGQI GdeGdjIs; (3GdGSJKeGQs